Hypervelocity impact flash and plasma on electrically biased spacecraft surfaces. (November 2018) - Hew, Y.M.; Goel, A.; Close, S.; Lee, N.
Highlights: Impact flash by micron-sized particles exhibit blackbody radiation in early time Strong dependence of plasma temperature on the impact target electrical bias New experimental evidence on impact plasma production of impact flash Impact flash temperature and optical thickness depends on impactor characteristics Abstract: Hypervelocity microparticles ( < 1 µg), traveling at speeds between 11 and 72 km/s with respect to the Earth, can impact spacecraft and form a small( ∼ 1 µm) and dense ( ∼ 10 23  m − 3 ) plasma. This plasma can generate a strong optical emission (impact flash) and electromagnetic pulse (EMP), which can lead to spacecraft electrical anomalies when the impacted spacecraft surface carries electrical potential due to various space weather effects. A parameter of the impact plasma that strongly determines its behavior is its temperature. In order to understand the microparticle hypervelocity impact plasma and their associated threat to spacecraft electronics, we need to determine the impact plasma temperature under different spacecraft charging conditions. A non-intrusive method to study the impact plasma is by measuring the optical emission spectrum. In this paper, we present a theory of how hypervelocity impact light flash is generated by the plasma, supported by experiments at a ground-based 3 MV electrostatic dust accelerator using three spectral photomultiplier tubes at 450, 550, and 600 nm. This paper is the first to present results on hypervelocity impacts with various target electrical biases as a control variable to study the relationship between the impact plasma and the impact flash. The impact flash continuum spectrum is suggested to be produced by the acceleration of charged particles via spacecraft surface electrical biases, the oscillating internal electric field, and/or the local recombination effects within the impact plasma. The impact flash was found to emit blackbody radiation in the early time after the impact ( ∼ 200 ns). Using blackbody spectrum to estimate the plasma temperature and optical thickness, we found that an impact velocity range of 15 to 40 km/s yielded average plasma temperatures between 3300 and 6000 K depending on the target biases. Our measurements demonstrated a strong dependence of plasma temperature on the bias, which serves as new experimental evidence to support that impact flash is produced by the impact plasma. The correlations between the impactor characteristics such as mass, velocity, and charge production are also connected with the temperature and optical thickness measurement.